EFEKTIVITAS PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP PENCAIRAN TUNGGAKAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO - Rumende, Hendro J.; Tinangon, Jantje; Pinatik, Sherly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
Tax is a source of income main every country in the world. of existence tax is important in the function state and government. In developed countries and developing world, partly potential state revenue through tax has been utilized for purposes improvement of innovation and technology business entities and industry national them. With taxes, a government can run policy relating to stabilitasi price inflation so that the rate can remain maintained. The purpose of this research is to determine the level effectiveness billing tax by using letter forcibly and warning and to know how big contribution billing tax with letters forcibly and warning on tax office pratama manado. Based on the data processing, can be seen distinction significantly. Whereby a level effectiveness billing taxes by warning and letters forcedly is larger in 2011 than 2012. Some things which causes an entirely warning and letters forcedly published can tertagih or repaid by companies to tax among others; the tax carelees in pay its debts tax underwriter tax not recognize the debt tax underwriter tax unable to pay its debts assessment. From data calculations in get that billing tax with with warning in 2011 and 2012 ineffective in compare to billing tax with letters forcedly belonging very effective. And contribution warning against disbursement arrears tax is lacking in compare with letters forcedly belonging good enough.